2019
DOI: 10.1182/blood-2019-129349
|View full text |Cite
|
Sign up to set email alerts
|

Improved Anti-Tumor Response of Chimeric Antigen Receptor T Cell (CART) Therapy after GM-CSF Inhibition Is Mechanistically Supported By a Novel Direct Interaction of GM-CSF with Activated Carts

Abstract: Despite the remarkable activity of CD19 directed chimeric antigen receptor T cell (CART19) therapy in the treatment of B cell malignancies, the therapy is limited by the development of severe life-threatening complications such as neurotoxicity (NT) and cytokine release syndrome (CRS). Additionally, durable efficacy following CART19 therapy is not optimal. Emerging literature suggests that inhibitory myeloid cells and their cytokines play an important role in inducing CAR-T cell toxicities and also contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We have recently shown that GM-CSF depletion results in modulation of apoptosis pathways in T cells. 22 It is unclear at this time if the increase in lymphocyte count is secondary to clearance of SARS-CoV-2 virus, or a direct effect of GM-CSF on T cells; this question will be answered in the planned phase III trial. Figure 3 Five patients received other pharmacotherapies targeting COVID-19 besides lenzilumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that GM-CSF depletion results in modulation of apoptosis pathways in T cells. 22 It is unclear at this time if the increase in lymphocyte count is secondary to clearance of SARS-CoV-2 virus, or a direct effect of GM-CSF on T cells; this question will be answered in the planned phase III trial. Figure 3 Five patients received other pharmacotherapies targeting COVID-19 besides lenzilumab.…”
Section: Discussionmentioning
confidence: 99%
“…21 GM-CSF depletion results in modulation of myeloid cell behavior, a specific decrease in their inflammatory cytokines, and a reduction in tissue trafficking, 21 while enhancing T-cell apoptosis machinery. 22 These biological effects prevented both CRS and neuro-inflammation after CART therapy in preclinical models and are being tested in a phase Ib/II clinical trial (NCT 04314843).…”
Section: Introductionmentioning
confidence: 99%
“…Sorbera et al claim SARS-Cov-induced apoptosis via a caspase-dependent mechanism may suggest inhibition of the Fas/FasL interaction may have efficacy in Sars-Cov-2, but the rationale disregards differentiation ( 45 ). Finally, in a CRISPR-Cas9 lentiviral vector knock out of GM-CSF in CAR T cells, Fas expression was significantly inhibited, which the authors argue would reduce CAR-T apoptosis ( 46 ), and GM-CSF inhibition trials are undergoing. Considering 1) the role the immune system may have in Covid-19 pathogenesis, 2) the observation that FasL is upregulated ( 21 ), and 3) that Fas signaling induces Akt-mediated differentiation, investigation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte-macrophage colony stimulating factor (GM-CSF) is upregulated and released by activated CAR T which may promote macrophage activation. 73 The critical role of GM-CSF is further evidenced in animal models by reductions in CRS severity observed both with GM-CSF blockade following CAR T 74 or with GM-CSF gene knockout CAR T. 75 Release of IL-6 is further stimulated by release of IL-1 from APCs. 76 CAR T and other activated T cells appear to be the primary source of interferon (IFN)-ɣ and IL-2 during CRS.…”
Section: Updates In Car T Toxicity Managementmentioning
confidence: 99%